ETIKA BISNIS ISLAM SENI BERBISNIS DALAM KEBERKAHAN - Dini Sentya Ningrum; Ivanka MiraNur Aini; Yunita Maulidiyah Faha; Eka Vebryl Maretha (Izdihar: Jurnal Ekonomi Syariah, 2021)
Islamic business ethics, namely as a set of values ​​about good, bad, right, and wrong as well as our attitudes and rules in the world that refer to business that refers to the Al-Quran and Hadith, in other words live the world according to Allah's commands and prohibitions. -His. Islamic business ethics is an ethical norm based on the Qur'an and Hadith that must be used as a way of life by business people. But in fact, many unscrupulous business people commit fraud so that they get out of the norm of Islamic business ethics. This study aims to describe and analyze comprehensively and thoroughly about the application of ethics applied by the company by doing business with blessings.